Family Communication in the Digital Era for Resolving Household Conflicts - Rajagukguk, Djudjur Luciana; Sriwartini , Yayu; Ramadhanis, Tamara (Department of Sociology, Universitas Nasional (Indonesia), 2026)
This study aims to analyze the application of family communication in resolving domestic conflict, focusing on conversation orientation, compliance, and interpersonal communication skills. The research method used a qualitative approach with a literature review of couples who had experienced domestic conflict. The results indicate that communication based on openness, mutual respect, and thirdparty mediation, when necessary, can reduce conflict intensity and improve the quality of family relationships. Therefore, implementing effective family communication is a key strategy in maintaining household stability and the psychological well-being of family members. Therefore, it is important to find effective solutions that can help resolve these conflicts. Communication is key in resolving conflict, with values such as compassion and patience helping to manage differences more effectively. This approach strengthens emotional and spiritual bonds, creating a more stable and healthy family environment.